2010
DOI: 10.1016/j.bbadis.2009.07.009
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial permeability transition pore: A molecular target for amyotrophic lateral sclerosis therapy

Abstract: Effective therapies are needed for the treatment of amyotrophic lateral sclerosis (ALS), a fatal type of motor neuron disease. Morphological, biochemical, molecular genetic, and cell/animal model studies suggest that mitochondria have potentially diverse roles in neurodegenerative disease mechanisms and neuronal cell death. In human ALS, abnormalities have been found in mitochondrial structure, mitochondrial respiratory chain enzymes, and mitochondrial cell death proteins indicative of some non-classical form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 166 publications
(276 reference statements)
1
58
0
Order By: Relevance
“…These mice undergo motor neuron degeneration with typical features of mitochondriopathy [140], suggesting the involvement of mitochondrial transition pores [141]. Although there is no available data to date, it is worth contemplating that mitochondrial PLA 2 (iPLA 2 and GIIA) contribute to mitochondrial dysfunction in this disease.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…These mice undergo motor neuron degeneration with typical features of mitochondriopathy [140], suggesting the involvement of mitochondrial transition pores [141]. Although there is no available data to date, it is worth contemplating that mitochondrial PLA 2 (iPLA 2 and GIIA) contribute to mitochondrial dysfunction in this disease.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…But high Ca 2+ concentrations (2 mM) still lead to mPTP opening and cell death in cyclophilin D knock out mice [120]. Thus, the effects of cyclophilin D deficiency on motor neurons need to be examined in more detail [22].…”
Section: Calmodulin and The Ca 2+ /Calmodulin-dependent Protein Kinasesmentioning
confidence: 99%
“…1). Once intramitochondrial Ca 2+ rises above a certain threshold, the voltage-and Ca 2+ -dependent high-conductance channel in the inner membrane, known as the mitochondrial permeability transition pore (mPTP) opens leading to cell death either by apoptosis or necrosis [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, mPTP is possibly located in the inner membrane pore and mainly responsible for calcium homeostasis and ROS generation (Halestrap, 2009). Another study has shown that mPTP consists of VDAC and ANT, Bax, Bcl-2, and cyclophilin D (Martin, 2010a). Regardless of these perspectives, mPTP is necessary to maintain the normal function of the mitochondria; after the mPTP opens, mitochondrial inner membrane potential collapses and ions between the matrix and the cytosol become imbalanced, the mitochondria swell as a result.…”
Section: Function Of Mitochondrial Channels In Mitochondrion-dependenmentioning
confidence: 98%